Efektivitas Pestisida Nabati Saliara (Lantana camara L.) Terhadap Kutu Daun (Aphis gossypii Glover) Pada Tanaman Tomat (Solanum lycopersicum L.) - Nabilla Anggie Prameswari Pramewari; Helda Orbani Rosa Rosa (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Tomatoes are an important horticultural commodity whose production is often disrupted by attacks by plant pests (OPT), especially the aphid Aphis gossypii. This pest damages plants by sucking cell fluids, causing wrinkling of leaves, chlorosis and stunted growth. Prolonged use of synthetic pesticides has the potential to cause problems such as pest resistance and accumulation of chemical residues. This research was conducted to determine the effectiveness of saliara leaf solution (Lantana camara L.) as an alternative to vegetable pesticides. Saliara leaves contain bioactive compounds of alkaloids, flavonoids, tannins, saponins and essential oils which are toxic to insects. The experiment used a completely randomized design (CRD) with one factor with four solution concentrations (35%, 45%, 50% and 75%) and one control and each with four replications. Parameters observed include pest mortality and attack intensity. The results showed that all solution concentrations were able to increase aphid mortality compared to the control. A 35% concentration produces the highest mortality, namely 100%, followed by a 75% concentration of 97.5% with a mechanism of action through contact and residue. The 75% and 50% treatments were also the most effective in suppressing attack intensity which remained below 1.5% until the third day, while the control increased to 8.68%.